The transcriptional repressor ICER and cAMP-induced programmed cell death - Ruchaud, Sandrine; Foulkes, Nicholas S. (Oncogene, 1997)
Oncogene is one of the world’s leading cancer journals. It is published weekly and covers all aspects of the structure and function of Oncogenes. Oncogene also publishes 8 Reviews issues a year, on a broad range of topics.